2016
DOI: 10.1007/s00167-016-4262-3
|View full text |Cite
|
Sign up to set email alerts
|

Return to sport after the surgical management of articular cartilage lesions in the knee: a meta-analysis

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(154 citation statements)
references
References 73 publications
7
135
1
1
Order By: Relevance
“…Microfracture is a very popular procedure to treat KOL. In fact, this is a simple, cheap, and usually fast-recovering operation with good results and return to sports rate [ 6 ]. However, the procedure creates a fibrocartilage with inferior biologic and biomechanical properties, which likely explains the potential worse long-term outcomes compared to cartilage regenerative techniques [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microfracture is a very popular procedure to treat KOL. In fact, this is a simple, cheap, and usually fast-recovering operation with good results and return to sports rate [ 6 ]. However, the procedure creates a fibrocartilage with inferior biologic and biomechanical properties, which likely explains the potential worse long-term outcomes compared to cartilage regenerative techniques [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondral autograft transfer delivers viable, mature hyaline cartilage-bone units into chondral defects. These osteochondral grafts can bear load in the early postoperative period, enabling faster rehabilitation than following other, currently available, cell-based cartilage repair strategies 26 . Osteochondral autograft transfer involves the harvesting of 'plugs' from regions of the distal femur that bear low loads (such as the intercondylar notch or medial or lateral trochlea) and, therefore, its use is reserved for small chondral defects (<2 cm 2 ) owing to limited graft availability 27 .…”
Section: Current Surgical Strategies Repairing Articular Cartilage Dementioning
confidence: 99%
“…Both osteochondral autograft transfer and osteochondral allograft transplantation have produced high rates of long-term graft survival, as well as high degrees of reported patient satisfaction and return-to-play among athletes 26,[33][34][35] . For example, a 2016 systematic review found that ~90% of patients who underwent osteochondral autograft transfer had good or excellent outcomes at up to 10 years after surgery 19 .…”
Section: Current Surgical Strategies Repairing Articular Cartilage Dementioning
confidence: 99%
“…16,17 However, patients treated for ACI have a higher proportion of PF lesions compared with other treatments, such as osteochondral allograft (OCA), microfracture (MFx), and osteochondral autograft tranfer (OAT). 16,18 Conversely, patients with PF cartilage lesions also more commonly undergo ACI instead of other treatments, such as OCA, MFx, and OAT, compared with patients with lesions in the femoral condyle. 19,20 A few factors contribute to this finding.…”
Section: Evaluation Of Outcomes and Long-term Recommendationsmentioning
confidence: 99%